STRATEGIES FOR MAINTAINING THE MENTAL HEALTH OF HEALTHCARE WORKERS (International Conference on Economics, Finance, Banking and Management, 2025)
This article highlights the urgency of maintaining the mental health of healthcare professionals. Physicians, nurses, and other medical personnel are frequently exposed to high levels of stress, emotional exhaustion, burnout syndrome, depression, and anxiety, especially intensified during the COVID-19 pandemic. The article analyzes the root causes and consequences of these psychological conditions and explores effective strategies to support mental well-being among healthcare workers. These strategies include psychological counseling, creating a supportive work environment, stress management training, ensuring adequate rest, and promoting a healthy lifestyle. Furthermore, the study examines international best practices, healthcare reforms, and the role of compassionate approaches in medical institutions. The findings demonstrate that maintaining mental health is a critical factor in improving the overall quality and sustainability of healthcare systems.